Beyond emotional labour: Emotions and peer support in a Canadian prison. (November 2019) - Walby, Kevin; Cole, Dwayne
Abstract: Little research has examined the emotional labour of prisoners working in the prison. Drawing from interviews with members of the Peer Offender Prevention Service (POPS) at a Canadian prison, which is an initiative whereby some prisoners trained in suicide prevention serve as mentors and guides for other prisoners experiencing distress, this paper examines how the work of POPS involves management of one's own emotions as well as the emotions of other prisoners. We reveal how this emotional labour happens in specific areas and spaces of the prison. However, drawing from other trends in the sociology of emotions, we also show how there are emotions beyond emotion management in the prison, which entails analyzing trust and confidence among POPS members, and exploring community and communal emotional climates. The paper makes an empirical contribution by adding to literature on emotions and prison conditions, as well as a conceptual contribution by advancing literature on emotional labour. Highlights: The first study of the emotional labour of prisoners in a male prison. The first study of the Peer Offender Prevention Service (POPS) at Stony Mountain Penitentiary in Manitoba, Canada. Reveals the spatial dynamics of how prisoners perform emotional labour as part of POPS work. Contributes to literature on emotional labour. Explores the collective effervescence that emerges for POPS members.